2008
DOI: 10.1152/ajprenal.00427.2007
|View full text |Cite
|
Sign up to set email alerts
|

Role of AQP2 in activation of calcium entry by hypotonicity: implications in cell volume regulation

Abstract: Galizia L, Flamenco MP, Rivarola V, Capurro C, Ford P. Role of AQP2 in activation of calcium entry by hypotonicity: implications in cell volume regulation. Am J Physiol Renal Physiol 294: F582-F590, 2008. First published December 19, 2007 doi:10.1152/ajprenal.00427.2007.-We previously reported in a rat cortical collecting duct cell line (RCCD1) that the presence of aquaporin 2 (AQP2) in the cell membrane is critical for the rapid activation of regulatory volume decrease mechanisms (RVD) (Ford et al. Biol Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 57 publications
(69 reference statements)
0
29
0
1
Order By: Relevance
“…] osmotic shrinkage/swelling also varies between cell types, being very high in EAT cells (see Fig. 1) and low in, e.g., rat cortical collecting duct cells (264). From the scanning electron micrographs in Figure 1, it is seen that the initial increase/decrease in cell volume involves unfolding/folding of the plasma membrane.…”
Section: Cell Volume Regulationmentioning
confidence: 94%
See 1 more Smart Citation
“…] osmotic shrinkage/swelling also varies between cell types, being very high in EAT cells (see Fig. 1) and low in, e.g., rat cortical collecting duct cells (264). From the scanning electron micrographs in Figure 1, it is seen that the initial increase/decrease in cell volume involves unfolding/folding of the plasma membrane.…”
Section: Cell Volume Regulationmentioning
confidence: 94%
“…As detailed below, the osmotic water permeability of animal cells is several orders of magnitude greater than the permeability towards Na ϩ , K ϩ , and Cl Ϫ . In many cell types, a high water permeability reflects the presence of aquaporins (AQPs), and it has been shown that the presence of AQP2 (cortical collecting duct cells) or AQP5 (salivary gland cells) dramatically increases the rate of initial cell swelling following hypotonic exposure (264,579). For a detailed description of the physiology of AQPs, see Reference 448.…”
Section: Introductionmentioning
confidence: 99%
“…We also established that this RVD is related to the activation of the cystic fibrosis transmembrane conductance regulator (CFTR) and to barium-sensitive potassium channels [Ford et al, 2005] causing the exit of K the intracellular calcium concentration ([Ca 2þ ] i ) that only occurs in the presence of AQP2 [Galizia et al, 2008]. In fact, wild-type cells not expressing AQP2 (WT-RCCD 1 ) showed a diminutive increase in [Ca 2þ ] i and were incapable of producing a rapid activation of RVD.…”
mentioning
confidence: 96%
“…In astrocytes and retinal Muller cells, TRPV4 is functionally linked to AQP4 (Benfenati et al, 2011;Jo et al, 2015), and this association is a requirement for RVD. TRPV4 associates with AQP5 in acinar and salivary gland cells (Liu et al, 2006;Hosoi, 2016) and with AQP2 in renal cells (Galizia et al, 2008).…”
mentioning
confidence: 99%